Fiscal integration and harmonization: European Union integration from fiscal perspectives - objectives, means, obstacles, and politics - (:unkn) unknown (IGI Global, 2014)
The concept of integration expresses an extremely fundamental and complicated formation. Despite such important and complicated issues and problems, Europe has made considerable progress and developments and been able to form the European Economic Community first and then the European Communities, and finally the European Union. It is necessary to precisely and smoothly complete the three stages of integration in order to mention about an exact integration. These stages, economic integration, fiscal integration, and political integration are discussed within this chapter. The first stage, economic integration, can be achieved only with the integration of the trade among the elements of the integration. Hence, it is required to seek for the fiscal harmonization of the tax legislation that is the most important competition breaker element in the field in question. A complete economic integration will be possible only by providing this fiscal harmonization. © 2015, IGI Global. All rights reserved.